AC/TiO2/Rubber Composite Sheet Catalysts; Fabrication, Characterization and Photocatalytic Activities - Chaval Sriwong; Worapol Tejangkura (My University, 2015)
The AC/TiO2/Rubber (ACTR) composite sheets weresuccessfully fabricated by a simply mixing of fixed TiO2 suspension and natural rubber latex (60% HA) contents withthe varyingamounts of activated carbon (AC) suspension, followed by stirring, pouring into apetri dish mold, drying at room temperature (RT), after that taking out from a mold, reversing and drying again at RT. Then, the as-fabricated ACTR composite sheets were characterized by X-ray diffractometer (XRD), attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR), energy dispersive X-ray spectroscopy (EDS) and scanning electron microscopy (SEM)techniques. The photocatalytic efficiencies of all ACTR composite sheet samples were evaluated by photo degrading of methylene blue (MB) dye solution under UV light irradiation. The results showed that the photocatalytic activity of ACTR sheet with10.0wt%AC loading has the highest efficiency for the photo degradation of MB dye than the other sheets. This is due to the fact that it is relatively with the synergistic effect of well-combined titanium dioxide catalyst and activated carbon adsorbent.
Keywords: Diffractometer; Titanium Dioxide; Suspension; TiO2 Photocatalysis and Solar Cells